2010
DOI: 10.1111/j.1469-8137.2010.03213.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of plant carotenoid biosynthesis through virus‐induced gene silencing affects oviposition behaviour of the butterfly Pieris rapae

Abstract: Summary• Optical plant characteristics are important cues to plant-feeding insects. In this article, we demonstrate for the first time that silencing the phytoene desaturase (PDS) gene, encoding a key enzyme in plant carotenoid biosynthesis, affects insect oviposition site selection behaviour.• Virus-induced gene silencing employing tobacco rattle virus was used to knock down endogenous PDS expression in three plant species (Arabidopsis thaliana, Brassica nigra and Nicotiana benthamiana) by its heterologous ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 56 publications
4
35
2
Order By: Relevance
“…Considering that a significant fraction of the shorter wavelengths is absorbed by chlorophylls (Gitelson et al, 2002), that carotenoids still have an average energy transfer efficiency of ;65%, and that for the blue wavelengths a est is up to 50% higher than a ( Figure 8), a considerable proportion of the quantum yield losses at the shorter wavelengths must be attributable to nonphotosynthetic pigments. The absorptance spectrum of the albino cucumber leaves (Figure 3) was similar to that found for albino leaf zones of Arabidopsis thaliana in which a gene encoding a key enzyme in carotenoid synthesis was knocked out by virus-induced gene silencing (Zheng et al, 2010). These absorptance spectra qualitatively indicate that nonphotosynthetic pigments absorbed at wavelengths <520 nm, which is in agreement with the lower values of a than those of a est (Figure 8).…”
Section: Origin Of the Wavelength Dependence Of Quantum Yieldsupporting
confidence: 78%
“…Considering that a significant fraction of the shorter wavelengths is absorbed by chlorophylls (Gitelson et al, 2002), that carotenoids still have an average energy transfer efficiency of ;65%, and that for the blue wavelengths a est is up to 50% higher than a ( Figure 8), a considerable proportion of the quantum yield losses at the shorter wavelengths must be attributable to nonphotosynthetic pigments. The absorptance spectrum of the albino cucumber leaves (Figure 3) was similar to that found for albino leaf zones of Arabidopsis thaliana in which a gene encoding a key enzyme in carotenoid synthesis was knocked out by virus-induced gene silencing (Zheng et al, 2010). These absorptance spectra qualitatively indicate that nonphotosynthetic pigments absorbed at wavelengths <520 nm, which is in agreement with the lower values of a than those of a est (Figure 8).…”
Section: Origin Of the Wavelength Dependence Of Quantum Yieldsupporting
confidence: 78%
“…Silencing of PDS resulted in photobleaching (Supplemental Fig. S5A), causing white patches and white leaves, and is therefore easily detected visually (Velásquez et al, 2009;Zheng et al, 2010). After 11 d, white patches and white leaves were observed, mainly in the newly formed leaves.…”
Section: Functional Analysis Of the Ros1-and Delactivated Genesmentioning
confidence: 99%
“…We employed a heterologous gene sequence, i.e., phytoene desaturase (BoPDS) from B. oleracea, to silence its ortholog in A. thaliana plants. We found that disruption of this specific gene of the carotenoid biosynthetic pathway through VIGS affected vision-mediated oviposition behavior of the butterfly Pieris rapae (Zheng et al, 2010). In the present study, we used B. oleracea gene sequences to silence two genes, lipoxygenase (AtLOX) and thioglucoside glucohydrolase: myrosinase (AtTGG) in A. thaliana plants because silencing BoLOX and BoMYR in cabbage plants themselves has not yet been successful.…”
Section: Introductionmentioning
confidence: 96%
“…Such VIGS vectors have been used to silence genes mainly in a number of solanaceous plant species, including tobacco, tomato, pepper, potato, and petunia (Shao et al, 2008). Optimized procedures aimed at improving the efficiency of agro-infiltration of A. thaliana have been reported in recent years (BurchSmith et al, 2006;Wang et al, 2006;Pflieger et al, 2008;Zheng et al, 2010). VIGS has obvious advantages over other known approaches for gene function analysis (Scofield and Nelson, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation